TiAlCrVSiN / TiAlCrVSiON nano multilayer composite tool coating and preparation method

The TiAlCrVSiN/TiAlCrVSiON nano multilayer composite tool coating addresses the limitations of existing coatings by enhancing hardness, wear resistance, and thermal stability through a multilayer structure design, improving performance in high-temperature and dry cutting environments.

CN116815115BActive Publication Date: 2024-12-20HUNAN CITY UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310059745.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-19
Publication Date
2024-12-20
Estimated Expiration
2043-01-19

AI Technical Summary

Technical Problem

Existing tool coatings lack high hardness, high-temperature oxidation resistance, and wear resistance, especially in dry cutting environments, and do not effectively reduce internal residual stress or improve bonding strength with substrates.

Method used

A TiAlCrVSiN/TiAlCrVSiON nano multilayer composite tool coating is prepared using self-generation technology and high-power magnetron sputtering, with alternating layers of TiAlCrVSiON and TiAlCrVSiN, optimized for thickness and oxygen content, to enhance thermal stability and wear resistance, and incorporate V for lubricity.

Benefits of technology

The coating achieves high hardness, low friction, excellent wear resistance, and improved bonding strength, suitable for high-speed cutting and dry cutting applications, with reduced residual stress and enhanced thermal stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116815115B_ABST
    Figure CN116815115B_ABST
Patent Text Reader

Abstract

The present invention discloses a TiAlCrVSiN / TiAlCrVSiON nano multilayer composite tool coating and a preparation method. The coating is prepared by using coating self-generation technology and high-power magnetron sputtering technology, and the coating includes: a TiAlCrN transition layer, an alternately deposited high-temperature resistant, oxygen-rich TiAlCrVSiON single layer and a high-hardness, nitrogen-rich TiAlCrVSiN single layer. The present invention uses self-generation coating technology and combines high-power pulsed magnetron sputtering deposition technology to obtain a nano multilayer composite tool coating with high hardness, toughness, good thermal stability and excellent high-temperature wear resistance; at the same time, by adjusting the modulation period, the residual stress inside the coating can be reduced and the coating density can be improved; the comprehensive mechanical properties of the coating can be further improved, and the process preparation process is simple and does not require additional costs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material surface treatment, and specifically discloses a self-generated TiAlCrVSiN / TiAlCrVSiON nano multilayer composite tool coating and a preparation method thereof. Background Art

[0002] With the rapid development of modern manufacturing industry, the application of difficult-to-process materials is becoming more and more extensive, which poses a more severe challenge to tool performance. Coated tools combine the advantages of high wear resistance, good oxidation resistance and substrate toughness of hard coatings, which significantly improves the cutting performance of tools and reduces processing costs. However, with the development of green processing technology, especially the widespread application of dry cutting technology, tool coatings need to have high hardness and excellent high-temperature oxidation resistance and wear resistance. At present, tool coatings are mainly single-coated, forming tool coatings with a specific function, which are difficult to meet processing requirements. By optimizing the coating structure design through coating self-generation technology and combining high-power pulsed magnetron sputtering technology, tool coatings with excellent high-temperature resistance and wear resistance can be prepared. At the same time, through the optimization design of multi-layer structure, the internal residual stress of the coating can be reduced, the thermal stability can be improved, and the compactness of the coating structure can be improved. It is one of the important development directions for improving the performance of hard tool coatings. Some nitride tool coatings have appeared. For example, CN107190229A discloses a method for preparing a self-assembled nano-oxynitride high-temperature resistant coating to form an alternating oxygen-rich CrAl(Si)ON / nitrogen-rich CrA(Si)ON coating. It has certain advantages over traditional coated tools in cutting high-temperature alloys, but the coating hardness performance is not particularly outstanding and the wear resistance needs to be improved. At the same time, the coating has no lubrication function and cannot effectively reduce the defects of coating wear. Summary of the invention

[0003] In order to solve the above problems, the present invention discloses a TiAlCrVSiN / TiAlCrVSiON nano multilayer composite tool coating having excellent high-temperature oxidation performance, high wear resistance and high thermal stability and a preparation method thereof.

[0004] The technical solution of the present invention is as follows:

[0005] The TiAlCrVSiN / TiAlCrVSiON nano multilayer oxynitride tool coating is prepared by using a coating self-generation technology and a high-power magnetron sputtering technology method, and includes: a TiAlCrN transition layer, an alternately deposited TiAlCrVSiON single layer and a TiAlCrVSiN single layer.

[0006] Preferably, the total thickness of the alternately deposited TiAlCrVSiON single layer and TiAlCrVSiN single layer is 2-3 μm, and the modulation period of the alternate deposition is 8.0-11.0 nm.

[0007] Preferably, the thicknesses of the alternately cyclically deposited TiAlCrVSiON layer and TiAlCrVSiN single layer are 2-3 nm and 5-6 nm respectively.

[0008] Preferably, the oxygen content in the TiAlCrVSiON single layer is 5.0-48 at.%, and more preferably, the oxygen content is 5.0-20 at.%.

[0009] Preferably, the thickness of the transition layer is 200-300 nm.

[0010] The preparation method of the TiAlCrVSiN / TiAlCrVSiON nano multilayer oxynitride tool coating comprises the following steps: (1) pre-treatment of the cemented carbide substrate before deposition; (2) preheating in a vacuum furnace; (3) bombarding the substrate surface with high-energy ions to remove impurities; (4) depositing a TiAlCrN transition layer; and (5) alternately depositing a high-temperature resistant TiAlCrVSiON single layer and a high-hardness TiAlCrVSiN single layer to form a nano multilayer oxynitride coating.

[0011] Furthermore, the cemented carbide substrate is a YT15 cemented carbide substrate.

[0012] Furthermore, in step (1), the pre-deposition treatment of the cemented carbide YT15 substrate includes the following steps: the substrate is ultrasonically cleaned with acetone, alcohol, and ionized water for 15 to 45 minutes each, then blown clean with compressed air and fixed on a rotating platform in a vacuum furnace at a rotation speed of 1 to 3 rpm.

[0013] Furthermore, in step (2), the vacuum furnace preheating includes the following steps: before the coating is deposited, the vacuum furnace is heated to 400°C to 500°C, and the background vacuum of the vacuum furnace is pre-evacuated to 1×10-4Pa.

[0014] Furthermore, in step (3), the high-energy ion bombardment of the surface to remove surface impurities includes the following steps: introducing Ar gas to raise the gas pressure in the furnace to 1.0-3.0 Pa, adjusting the substrate bias voltage to -600--400 V, and then bombarding and cleaning the cemented carbide substrate with high-energy Ar ions for 10-20 minutes to remove impurities and oxidation products on the substrate surface; turning on the TiAlCr target, and then adjusting the ion source power to 1.5-3.0 kW, the substrate bias voltage to -600--1000 V, and performing high-energy ion sputtering to remove impurities remaining on the cemented carbide substrate again.

[0015] Furthermore, in step (4), the TiAlCrN transition layer deposition includes the following steps: keeping other parameters of step (3) unchanged, reducing the substrate bias voltage to -70 to -100 V and the deposition temperature to 300 to 400°C; then adjusting the N2 gas flow rate to reduce the working gas pressure to 1.0 to 1.5 Pa, the coating deposition time is 10 to 20 minutes, and the TiAlCrN transition layer thickness is 200 to 300 nm.

[0016] Furthermore, in step (5), the alternate deposition of high temperature resistant TiAlCrVSiON single layer and high hardness TiAlCrVSiN single layer comprises the following steps: turning off the TiAlCr target and turning on the Ti 20 Al 50 Cr 20 For V5Si5 target deposition, the ion source power was adjusted to 1.5-2.0 kW, nitrogen and oxygen were introduced, the nitrogen flow rate was 550 sccm, the oxygen flow rate was 50 sccm, the total flow rate was 600 sccm, the substrate bias was added to -90--70 V, the deposition time was 100-150 min, the total deposition thickness was 2-3 μm, and the modulation period of alternating deposition was 8.0-11.0 nm.

[0017] Furthermore, in the step (5), the thicknesses of the oxygen-rich TiAlCrVSiON layer and the nitrogen-rich TiAlCrVSiN single layer deposited in alternating cycles are 2-3 nm and 5-6 nm, respectively.

[0018] Based on this, the present invention also provides a cutting tool, comprising the above-mentioned coating.

[0019] The design mechanism of the present invention is as follows:

[0020] The present invention adds O element into the TiAlCrVSiN coating by self-generation technology, and utilizes the excellent high-temperature thermal stability and high thermal resistance of the TiAlCrVSiON layer to improve the heat resistance of the multilayer coating; the TiAlCrVSiN layer and the TiAlCrVSiON layer are overlapped to form a nano multilayer composite coating, which can make the TiAlCrVSiN / TiAlCrVSiON nano multilayer composite coating have the characteristics of significantly excellent single-layer coating, forming a tool coating with good high-temperature thermal stability and high wear resistance; adopts high-power magnetron sputtering technology to improve the density of the coating structure, reduce the internal defects of the coating, and increase the high-temperature oxidation resistance and wear resistance of the coating. Thus, the processing environment requirements such as high-speed cutting and dry cutting are met. In addition, the V element is added to increase the lubricity of the coating and reduce the wear of the coating; the residual stress inside the coating is reduced by multilayer structure design, and the density of the coating is improved, thereby further improving the bonding strength between the coating and the cemented carbide substrate. At the same time, the process preparation process of the present invention is simple and does not require additional costs.

[0021] The advantages of the present invention are as follows:

[0022] 1. The TiAlCrVSiN / TiAlCrVSiON nano multilayer composite coating prepared by the present invention has the characteristics of high hardness, low friction coefficient, good wear resistance and lubrication between coatings.

[0023] 2. The TiAlCrVSiN / TiAlCrVSiON nano multilayer composite coating prepared by the present invention has excellent high temperature wear resistance and is suitable for the field of high-speed cutting processing. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The schematic diagram of the principle of the TiAlCrVSiN / TiAlCrVSiON coating process preparation process and the tool structure of the present invention;

[0025] Among them, 0-transition layer (increases membrane-substrate bonding strength), 1-high temperature oxidation resistance layer, 2-high hardness wear-resistant layer;

[0026] Figure 2 Surface and cross-sectional SEM morphologies of TiAlCrVSiN / TiAlCrVSiON nano-multilayer coatings with different oxygen contents: 0at.% (A and G), 5.3at.% (B and H), 10.6at.% (C and I), 20.3at.% (D and J), 30.47at.% (E and K), 47.7at.% (F and O). 20 Al 50 Cr 20 V5Si5 target, current 80A, nitrogen flow rate 550sccm, oxygen flow rate 50sccm, total flow rate 600sccm, substrate bias voltage -80V;

[0027] Figure 3 XRD pattern of TiAlCrVSiN / TiAlCrVSiON nano multilayer coating. 20 Al 50 Cr 20 V5Si5 target, ion source power of 2.5kw, nitrogen flow rate of 550sccm, oxygen flow rate of 50sccm, total flow rate of 600sccm, substrate bias voltage of -80V;

[0028] Figure 4 are the hardness and elastic modulus of TiAlCrVSiN / TiAlCrVSiON nano multilayer coatings with different oxygen contents. 20 Al 50 Cr 20V5Si5 target, ion source power of 2.5kw, nitrogen flow rate of 550sccm, oxygen flow rate of 50sccm, total flow rate of 600sccm, substrate bias voltage of -80V;

[0029] Figure 5 Panoramic image of scratches on TiAlCrVSiN / TiAlCrVSiON nano-multilayer coatings with different oxygen contents. 20 Al 50 Cr 20 V5Si5 target, ion source power of 2.5kw, nitrogen flow rate of 550sccm, oxygen flow rate of 50sccm, total flow rate of 600sccm, substrate bias voltage of -80V;

[0030] Figure 6 Wear morphologies of TiAlCrVSiN / TiAlCrVSiON, TiAlCrVSiON and TiAlCrVSiN coatings at 800°C: (a) TiAl CrVSiN / TiAl CrVSiON coating deposited by self-generated coupled high-power pulsed magnetron sputtering technology, (b) TiAl CrVSiN / TiAl CrVSiON coating deposited by self-generated coupled cathodic arc ion plating technology, (c) TiAl CrVSiON coating deposited by high-power pulsed magnetron sputtering technology, (d) TiAlCrVSiN coating deposited by high-power pulsed magnetron sputtering technology, Ti 20 Al 50 Cr 20 V5Si5 target, ion source power is 2.5kw, nitrogen flow rate is 550sccm, oxygen flow rate is 50sccm, total flow rate is 600sccm, substrate bias is -80V.

[0031] Figure 7 Three-dimensional wear morphologies of TiAl CrVSiN / TiAl CrVSiON, TiAl CrVSiON and TiAl CrVSiN coatings at 800°C: (a) TiAl CrVSiN / TiAlCrVSiON coating deposited by self-generated coupled high-power pulsed magnetron sputtering technology, (b) TiAl CrVSiN / TiAl CrVSiON coating deposited by self-generated coupled cathodic arc ion plating technology, (c) TiAl CrVSiON coating deposited by high-power pulsed magnetron sputtering technology, (d) TiAl CrVSiN coating deposited by high-power pulsed magnetron sputtering technology, Ti 20 Al 50 Cr 20V5Si5 target, ion source power is 2.5kw, nitrogen flow rate is 550sccm, oxygen flow rate is 50sccm, total flow rate is 600sccm, substrate bias is -80V.

[0032] Figure 8 are the friction coefficient and wear rate of the wear scar of TiAl CrVSiN / TiAl CrVSiON, TiAl CrVSiON and TiAl CrVSi N coatings;

[0033] (a) Friction coefficient of different coatings at 800℃, (b) Wear rate of coatings at different temperatures, Ti 20 Al 50 Cr 20 V5Si5 target, ion source power is 2.5kw, nitrogen flow rate is 550sccm, oxygen flow rate is 50sccm, total flow rate is 600sccm, substrate bias is -80V. DETAILED DESCRIPTION

[0034] The technical solutions in the implementation cases of the present invention are described clearly and completely below. The described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] The reagents or instruments used in the examples of the present invention without indicating the manufacturer are all conventional reagent products that can be obtained through commercial purchase.

[0036] Example 1

[0037] Preparation Example

[0038] Preparation of a TiAl CrVSiN / TiAl CrVSiON nano multilayer composite tool coating, such as Figure 1 As shown, it is prepared by adopting self-generated technical structure optimization design and high-power magnetron sputtering method. When the substrate is located at position ① close to the target source, a nitrogen-rich nitride layer is generated; when the substrate is far away from the target source, an oxygen-rich layer is generated at positions ②③④; by rotating the substrate, nitrogen-rich layers and oxygen-rich layers of nitride oxide nano-multilayers are alternately generated to form a nitride oxide coating with high hardness, good high-temperature thermal stability and wear resistance; through high-power pulsed magnetron sputtering technology, the comprehensive performance of the coating is improved, and the wear resistance of the coating is further improved.

[0039] The specific steps include:

[0040] (1) Pretreatment of cemented carbide substrate deposition: The cemented carbide substrate YT15 was ultrasonically cleaned with acetone, alcohol, and ionized water for 15 min each, then cleaned with compressed clean air and placed on a rotating platform in a deposition furnace at a rotation speed of 1 rpm.

[0041] (2) Preheating of vacuum furnace: Before depositing the coating, heat the vacuum furnace to 400°C and pre-evacuate the vacuum furnace to a vacuum of 1×10 -4 Pa;

[0042] (3) High-energy ion bombardment to remove impurities: Ar gas was introduced to raise the pressure in the vacuum furnace to 1.0 Pa, and then the substrate bias voltage was adjusted to -600 V. The cemented carbide substrate was cleaned by Ar ion bombardment for 15 min to remove impurities and oxidation products on the surface of the cemented carbide substrate. Subsequently, the TiAl Cr magnetron target was turned on, the ion source power was adjusted to 1.0 kW, the substrate bias voltage was adjusted to -600 V, and high-energy ion sputtering was performed to remove the impurities remaining on the cemented carbide substrate again.

[0043] (4) Deposition of transition layer TiAlCrN: keeping other parameters unchanged in step (3), the substrate bias voltage was reduced to -70 V, the deposition temperature was reduced to 300°C, and the ion source power was adjusted to 1.5 kW; then the N2 gas pressure and flow rate were adjusted to make the working gas pressure to 1.0 Pa, the deposition time was 10 min, and the thickness of the TiAlCrN transition layer was 200 nm;

[0044] (5) Alternately deposit high temperature resistant oxygen-rich TiAl CrVSiON single layer and high hardness nitrogen-rich TiAl CrVSiN single layer: turn off the TiAl Cr target and turn on the Ti 20 Al 50 Cr 20 V5Si5 target was deposited alternately, the ion source power was adjusted to 2.0 kW, the deposition time was 150 min, the nitrogen flow rate was 500 sccm, the oxygen flow rate was 20 sccm, the total flow rate was 520 sccm, the substrate bias was added to -70 V, the total deposition thickness was 2 μm, and the modulation period of the alternate deposition was 8.0 nm.

[0045] Example 2

[0046] Preparation Example

[0047] A TiAl CrVSiN / TiAl CrVSiON nano-multilayer composite tool coating is prepared by using a self-generated technology structure optimization design and a high-power magnetron sputtering method, such as Figure 1As shown, it is prepared by adopting self-generated technical structure optimization design and high-power magnetron sputtering method. When the substrate is located at position ① close to the target source, a nitrogen-rich nitride layer is generated; when the substrate is far away from the target source, an oxygen-rich layer is generated at positions ②③④; by rotating the substrate, nitrogen-rich layers and oxygen-rich layers of nitride oxide nano-multilayers are alternately generated to form a nitride oxide coating with high hardness, good high-temperature thermal stability and wear resistance; through high-power pulsed magnetron sputtering technology, the comprehensive performance of the coating is improved, and the wear resistance of the coating is further improved.

[0048] The specific steps include:

[0049] (1) Pretreatment of cemented carbide substrate deposition: The cemented carbide substrate YT15 was ultrasonically cleaned with acetone, alcohol, and ionized water for 30 min each, then blown clean with compressed clean air and fixed on a rotating platform in a deposition furnace at a rotation speed of 2.0 rpm;

[0050] (2) Preheating of vacuum furnace: Before depositing the coating, heat the vacuum furnace to 450°C and pre-evacuate the vacuum furnace to a vacuum of 1×10 -3 Pa;

[0051] (3) Surface impurity removal by ion bombardment: Ar gas was introduced to raise the pressure in the vacuum furnace to 2 Pa, and then the substrate bias voltage was adjusted to -500 V. The cemented carbide substrate was cleaned by Ar ion bombardment for 30 min to remove impurities and oxidation products on the surface of the cemented carbide substrate. Subsequently, the TiAl Cr magnetron target was turned on, the ion source power was adjusted to 1.5 kW, and the substrate bias voltage was adjusted to -800 V. High-energy ion sputtering was performed to remove the impurities remaining on the cemented carbide substrate again.

[0052] (4) Deposition of transition layer TiAlCrN: keeping other parameters unchanged in step (3), the substrate bias voltage was reduced to -85V, the deposition temperature was reduced to 350°C, and the ion source power was adjusted to 2.0 kW; then the N2 gas pressure flow was adjusted to make the working gas pressure to 1.2 Pa, the deposition time was 15 min, and the thickness of the TiAlCrN transition layer was 250 nm;

[0053] (5) Alternately deposit high temperature resistant oxygen-rich TiAl CrVSiON single layer and high hardness nitrogen-rich TiAl CrVSiN single layer: turn off the TiAl Cr target and turn on the Ti 20 Al 50 Cr 20 For V5Si5 target deposition, the ion source power was adjusted to 2.5 kW, the deposition time was 120 min, the nitrogen flow rate was 550 sccm, the oxygen flow rate was 50 sccm, the total flow rate was 600 sccm, the substrate bias was increased to -80 V, the total deposition thickness was 2.5 μm, and the modulation period of alternating deposition was 9.4 nm.

[0054] Example 3

[0055] A superhard nano multilayer composite tool coating with excellent high temperature resistance and wear resistance is prepared by using self-generated technology structure optimization design and high-power magnetron sputtering method, such as Figure 1 As shown, it is prepared by adopting self-generated technical structure optimization design and high-power magnetron sputtering method. When the substrate is located at position ① close to the target source, a nitrogen-rich nitride layer is generated; when the substrate is far away from the target source, an oxygen-rich layer is generated at positions ②③④; by rotating the substrate, nitrogen-rich layers and oxygen-rich layers of nitride oxide nano-multilayers are alternately generated to form a nitride oxide coating with high hardness, good high-temperature thermal stability and wear resistance; through high-power pulsed magnetron sputtering technology, the comprehensive performance of the coating is improved, and the wear resistance of the coating is further improved.

[0056] The specific steps include:

[0057] (1) Pretreatment of cemented carbide substrate deposition: The cemented carbide substrate YT15 was ultrasonically cleaned with acetone, alcohol, and ionized water for 45 min each, then cleaned with compressed clean air and placed on a rotating platform in a deposition furnace at a rotation speed of 3 rpm.

[0058] (2) Preheating of vacuum furnace: Before depositing the coating, heat the vacuum furnace to 500°C and pre-evacuate the vacuum furnace to a vacuum of 1×10 -2 Pa;

[0059] (3) Surface impurity removal by ion bombardment: Ar gas was introduced to raise the pressure in the vacuum furnace to 3 Pa, and then the substrate bias voltage was adjusted to -400 V. The cemented carbide substrate was cleaned by Ar ion bombardment for 45 min to remove impurities and oxidation products on the surface of the cemented carbide substrate. Subsequently, the TiAlCr magnetron target was turned on, the ion source power was adjusted to 2 kW, and the substrate bias voltage was adjusted to -1000 V. High-energy ion sputtering was performed to remove the impurities remaining on the cemented carbide substrate again.

[0060] (4) Deposition of transition layer TiAlCrN: keeping other parameters unchanged in step (3), the substrate bias voltage was reduced to -100 V, the deposition temperature was reduced to 400°C, and the ion source power was adjusted to 2.5 kW; then the N2 gas pressure and flow rate were adjusted to make the working gas pressure to 1.5 Pa, the deposition time was 20 min, and the thickness of the TiAlCrN transition layer was 300 nm;

[0061] (5) Alternately deposit high-hardness nitrogen-rich TiAlCrVSiN single layer and high-temperature resistant oxygen-rich TiAlCrVSiON single layer: turn off the Cr target and turn on the Ti 20 Al 50 Cr 20For V5Si5 target deposition, the ion source power was adjusted to 3.0 kW, the deposition time was 100 min, the nitrogen flow rate was 580 sccm, the oxygen flow rate was 70 sccm, the total flow rate was 650 sccm, the substrate bias voltage was increased to -90 V, the total deposition thickness was 3 μm, and the modulation period of alternating deposition was 11 nm.

[0062] Performance Testing

[0063] The superhard nano multilayer composite tool coating prepared in Example 2 was tested, and its structural schematic diagram is shown in the attached figure. Figure 1 shown.

[0064] Coating structure observation:

[0065] The coating morphology was observed by SEM. Figure 2 As shown. Figure 2 It can be found from Figure AF that when the oxygen content is lower than 5.3 at.%, the large particles on the surface of the TiAl CrVSiN / TiAl CrVSiON multilayer coating are smaller. As the oxygen content increases, the large particles increase significantly. Figure 2 The cross-sectional morphology of (GO) shows that the multilayer structure makes the coating structure dense and there is no obvious columnar crystal structure. It can be seen that the TiAl CrVSiN / TiAl CrVSiON multilayer coating greatly improves the quality and performance of the coating. The coating phase structure was studied by XRD, and the results are as follows Figure 3 As shown in the figure, as the oxygen content increases, the phase structure of the multilayer structure remains basically consistent, consisting of a cubic phase, which shows that the TiAl CrVSiN / TiAl CrVSiON multilayer coating maintains structural stability. In general, when the oxygen content of the TiAl CrVSiON single layer in the coating is 5.0-48at.%, the multilayer composite coating has a dense structure and good stability.

[0066] Coating mechanics, high temperature oxidation performance and tribological performance tests:

[0067] Nanoindenter was used to test the hardness and elastic modulus of the coating, scratch tester was used to test the coating film-substrate bonding strength, and high temperature friction and wear tester was used to study the tribological properties of the coating in high temperature environment. Figure 4 It can be found that the TiAlCrVSiN / TiAl CrVSiON nano multilayer coating has high hardness when the oxygen content is low (≤5.0at.%), and its microhardness reaches 37.2GPa (3795.8Hv). Figure 5It can be seen that the TiAl CrVSi N / TiAl CrVSiON nano multilayer coating also significantly improves the coating film-substrate bonding strength. At low oxygen content (5.3at.%O), its bonding force reaches 80.1N. The friction and wear experiment of the coating also clearly concluded that the TiAl CrVSiN / TiAl CrVSiON nano multilayer coating also significantly reduces the high-temperature friction coefficient of the coating and improves the high-temperature wear resistance of the coating. At a high temperature of 800℃, the friction coefficient of the TiAl CrVSiN / TiAl CrVSiON nano multilayer coating generated by the self-generated coupled high-power pulsed magnetron technology is reduced to about 0.3, while the average friction coefficients of the TiAl CrVSiON and TiAl CrVSiN single-layer coatings reach 0.82 and 0.71, respectively. Figure 8 (a) is shown. In general, when the oxygen content of the TiAlCrVSiON single layer in the coating is 5.0-20at.%, the multilayer composite coating has high hardness, high bonding strength between coatings, and good wear resistance. At the same time, the addition of V element improves the lubrication effect of the coating, reducing the friction coefficient of the TiAlCrSiN / TiAlCrSiON coating from about 0.5 to the friction coefficient of the TiAlCrVSiN / TiAlCrVSiON-2 coating of 0.3, as shown in Figure 2. Figure 8 As shown in (a), the wear rate is also greatly reduced at a high temperature of 800°C. Figure 8 (b) as shown.

[0068] It can be seen from the above examples that (1) the present invention can obtain a self-generated nano multilayer composite tool coating with high hardness and good high-temperature wear resistance through the optimization design of the multilayer structure. At the same time, by adjusting the modulation period, the internal structure of the coating can be reduced, the density of the coating can be improved, and the comprehensive mechanical properties of the coating can be further improved. (2) The process preparation process of the present invention is simple and does not require additional costs.

[0069] The above-mentioned embodiments only express a limited number of preferred implementations of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. TiAlCrVSiN / TiAlCrVSiON nano multilayer nitride oxide tool coating, characterized in that: The coating is prepared by using a coating self-generation technology and a high-power magnetron sputtering technology. The coating includes: a TiAlCrN transition layer, an alternately deposited TiAlCrVSiON single layer and a TiAlCrVSiN single layer. The preparation method includes the following steps: (1) pre-treatment of a cemented carbide substrate before deposition; (2) preheating in a vacuum furnace; (3) bombarding the substrate surface with high-energy ions to remove impurities; (4) depositing a TiAlCrN transition layer; (5) alternately depositing a high-temperature resistant TiAlCrVSiON single layer and a high-hardness TiAlCrVSiN single layer to form a nano multilayer nitride oxide coating; In step (3), the high-energy ion bombardment of the surface to remove surface impurities includes the following steps: introducing Ar gas to raise the gas pressure in the furnace to 1.0~3.0 Pa, adjusting the substrate bias voltage to -600~-400 V, and then bombarding the cemented carbide substrate with high-energy Ar ions for 10~20 minutes to remove impurities and oxidation products on the substrate surface; turning on the TiAlCr target, and then adjusting the ion source power to 1.5~3.0 kW, the substrate bias voltage to -600~-1000 V, and performing high-energy ion sputtering to remove impurities remaining on the cemented carbide substrate again; In step (4), the TiAlCrN transition layer deposition includes the following steps: according to the other parameters of step (3), the substrate bias voltage is reduced to -70~-100V, and the deposition temperature is reduced to 300~400°C; then the N2 gas flow rate is adjusted to reduce the working gas pressure to 1.0~1.5 Pa, the coating deposition time is 10~20min, and the TiAlCrN transition layer thickness is 200~300nm; In step (5), the alternate deposition of high temperature resistant TiAlCrVSiON single layer and high hardness TiAlCrVSiN single layer comprises the following steps: closing the TiAlCr target and opening the Ti 20 Al 50 Cr 20 For V5Si5 target deposition, the ion source power was adjusted to 1.5~2.0 kW, nitrogen and oxygen were introduced, the nitrogen flow rate was 550 sccm, the oxygen flow rate was 50 sccm, the total flow rate was 600 sccm, the substrate bias was added to -90~ -70 V, the deposition time was 100~150 min, the total deposition thickness was 2~3 μm, and the modulation period of alternating deposition was 8.0~11.0 nm.

2. The TiAlCrVSiN / TiAlCrVSiON nano multilayer oxynitride tool coating according to claim 1, characterized in that: The thicknesses of the alternately deposited TiAlCrVSiON layer and TiAlCrVSiN single layer are 2-3 nm and 5-6 nm respectively.

3. The TiAlCrVSiN / TiAlCrVSiON nano multilayer oxynitride tool coating according to claim 1, characterized in that: The thickness of the transition layer is 200-300 nm.

4. The TiAlCrVSiN / TiAlCrVSiON nano multilayer oxynitride tool coating according to claim 1, characterized in that: In step (1), the cemented carbide substrate deposition pretreatment includes the following steps: the substrate is ultrasonically cleaned with acetone, alcohol, and ionized water for 15 to 45 minutes each, then blown clean with compressed air and placed on a rotating platform in a vacuum furnace and fixed at a rotation speed of 1 to 3 rpm.

5. The TiAlCrVSiN / TiAlCrVSiON nano multilayer oxynitride tool coating according to claim 1, characterized in that: In step (2), the vacuum furnace preheating treatment includes the following steps: before coating deposition, heating the vacuum furnace to 400°C to 500°C, and pre-evacuating the vacuum furnace to a background vacuum of 1×10 -4 Pa.

Citation Information

Patent Citations

  • Self-assembled nano oxynitride high-temperature-resisting coating and preparing method thereof

    CN107190229A

  • Preparation process of AlCrTiSiN / AlCrTiSiON multilayer composite coating

    CN111647856A

  • Low-density biphase high-entropy alloy powder suitable for 3DP technology and preparation method of low-density biphase high-entropy alloy powder

    CN112692275A

  • Self-organizing nanostructure oxynitride hard coating and preparation method and application thereof

    CN113174562A